On-line FTIR spectroscopy system for extrusion-based process analysis - Barros Junior, Lucivan Pereira (Universidade Federal de São Carlos, 2021)
Polymer processing is a fundamental key to achieve the desired properties to reach the needs of polymer applications. Thus, it is important to understand how the processing can contribute to material characteristics during the extrusion, while they are being processed. That is why this work propose a method able to perform analyses of the material while it is being processed during the extrusion: the on-line Fourier transform infrared (FTIR) spectroscopic system. The system consists of a device that was designed to be able to couple a commercial infrared spectrometer to an twin-screw extruder. On-line FTIR measurements can be done in different locations along the extruder barrel. Pearson VII function was used improving the linearity of mixture composition, which is proposed by Beer-Lambert’s law, by around 14% when compared to the traditional methods. Polymer blends of polypropylene (PP) and polyamide 6 (PA6) at different weight composition ratio were used to validate the on-line system during extrusion. The area ratio between the IR bands at 1640 cm−1 (υC=O) and 1373 cm−1 (σC-H3) were measured on-line for all the blend compositions and shown to be in good agreement with off-line measurements. When the reactive blending of polyamide 6 (PA6) and polypropylene grafted with acrylic acid (PP-g-AA) (in blends of 80%/20% and 30/70% of PP-g-AA and PA6, respectively) was investigated along the extruder length, a increase of the IR band area ratio (1640/1373 cm−1) was achieved when the process condition aggressiveness in mixing was improved due to the generation of fresh interface between the two phases, as it is shown through scanning electron microscopy (SEM). Trough on-line FTIR measurements it was possible to visualize the development of the reactive blending reaction of PP-g- AA/PA6 blends inside the extruder. For example, different process conditions lead to the same or different amount of reaction (IR area ratio 1640/1373 cm−1) at the end of the extruder, but they follow different rates and times.
Sistema on-line de espectroscopia de infravermelho com transformada de Fourier para análise de processos baseados em extrusão
Keywords: Reactive extrusion; Polymer blends; FTIR; On-line analysis; In-processing analysis; Extrusão reativa; Blendas polimericas; FTIR; Analises on-line; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS